2005
DOI: 10.1007/bf02893039
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical diagnosis of alcoholism

Abstract: Medically diagnosed alcoholics can be differentiated reliably from non-alcoholics using clinically laboratory tests. In the present study, patients with liver diseases either due to alcohol or without alcohol compared with a group of normal healthy persons. Heavy drinkers showed significantly lower body weight and percent body fat, and low BMI compared with other groups. The percentage of hemoglobin and total number of RBC were found to be significantly decreased, whereas mean corpuscular volume (MCV) signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 25 publications
4
33
1
Order By: Relevance
“…Addolorato et al, [19] observed that alcoholics, as compared with social drinkers showed a lower body weight due to reduction of fat mass and other study, World et al, [20] shows that reduce body weight was the best clinical indicator of apparently of the alcohol abuse. We observed, the increase levels of AST, ALT, ALP, GGT, and total bilirubin in alcoholic liver disease, our study compression of Das SK et al, [21] have shows that the significant levels of serum alanine aminotransfrase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and ã-glutamyltransferase (GGT) activities were observed in alcoholic liver in comparison to healthy controls. Levels of alkaline phosphatase are also helpful in identifying the cause and severity of liver damage.…”
Section: Resultssupporting
confidence: 59%
“…Addolorato et al, [19] observed that alcoholics, as compared with social drinkers showed a lower body weight due to reduction of fat mass and other study, World et al, [20] shows that reduce body weight was the best clinical indicator of apparently of the alcohol abuse. We observed, the increase levels of AST, ALT, ALP, GGT, and total bilirubin in alcoholic liver disease, our study compression of Das SK et al, [21] have shows that the significant levels of serum alanine aminotransfrase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and ã-glutamyltransferase (GGT) activities were observed in alcoholic liver in comparison to healthy controls. Levels of alkaline phosphatase are also helpful in identifying the cause and severity of liver damage.…”
Section: Resultssupporting
confidence: 59%
“…The results of the present study are in concordance with that of the earlier studies. [3,4,5,6,7,8] Earlier studies conducted on cohort of individuals with alcohol dependence have found to have raised Erythrocyte Sedimentation Rate especially in patient with alcohol liver disease. [15] In the current investigation 23.8% of individuals with alcohol dependence syndrome in withdrawal state and 32.4% of individuals with alcohol dependence syndrome in delirium have raised Erythrocyte Sedimentation Rate.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of hemoglobin and total number of red blood cells was found to be significantly decreased. [3,4] It was also observed that patients with chronic alcohol consumption was associated with iron deficiency anaemia, alcohol-induced haemolytic anaemia with liver damage. [5,6] Haematological studies conducted on 65 consecutive patients with alcohol dependence syndrome found that 75% of the patients had disorders of red blood cells production, 40% had megaloblastic erythropoiesis secondary to folic acid deficiency, 30% had ring sideroblastic defect of the marrow and also other causes of anaemia such as haemorrhage, infections or iron deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have demonstrated that both low and moderate levels of chronic alcohol consumption are associated with an increased BMI (Conigrave et al2003a) and that they cause varying degrees of liver damage, with elevated ALT (Conigrave et al2003b), AST (Conigrave et al2003c), ALP (Das and Vasudevan 2005) and GGT levels (Conigrave et al2003d;Hietala et al 2005;Das and Vasudevan 2005;Grasselli et al 2014) and even moderate/severe hepatic steatosis (Conigrave et al2003e). However, another study has reported conflicting results, showing that heavy drinkers have a significantly lower body weight, percent body fat, and BMI compared with non-heavy drinkers (Das and Vasudevan 2005). Therefore, the influences of the severity of drinking on the body weight, percent body fat, and BMI differ, but the cause of these differences remains unclear and requires further elucidation.…”
Section: Discussionmentioning
confidence: 99%